Trends in Sustainable Bakery: A systematic Review of Alternative Ingredients Derived from Tubers, Legumes, and Insects in Indonesia - Nadina Hajar Annisa Alasimi; Putri Marini Ghaisani (Universitas Negeri Semarang, 2026)
The global shift toward sustainable and functional foods has encouraged the development of innovative alternative ingredients in bakery products. In Indonesia, the high dependence on imported wheat flour poses challenges to food security, driving the exploration of local substitutes. This systematic literature review aims to analyze the potential, characteristics, and challenges of utilizing alternative ingredients derived from tubers, legumes, and insects for sustainable bakery production in Indonesia. The study reviewed 25 national and international scientific publications from 2015–2025, focusing on nutritional composition, sensory acceptance, and technological applications. Findings indicate that tuber-based flours (such as modified cassava flour and taro) and legume-based flours (soybean, mung bean) can replace up to 30% of wheat flour without significantly affecting product quality. In contrast, insect-based flours particularly cricket flour offer high protein and micronutrient potential but still face consumer acceptance barriers. This review contributes by consolidating multidisciplinary evidence and proposing a practical framework for reducing wheat dependency through local ingredient utilization offering actionable insights for researchers, policymakers, and the bakery industry toward a more sustainable food system in Indonesia.